The Effect of Organizational Commitment, Organizational Culture, Work Environment, and Leadership Style on Job Satisfaction - Sri Langgeng Ratnasari; Endiet Jaloe Prasetiyo; Lukmanul Hakim (Enrichment : Journal of Management, 2020)
The purpose of this studies to analyze organizational commitment, organizational culture, work environment to job satisfaction of employee of PT. BintanBersatu Apparel Batam partially and simultaneously. This research is quantitative from primary sources collected through questionnaires. The data technique of collection is Cluster Sampling. The data analysis used is the testing instrument carried out through testing validity and reliability, while the analysis of data technique used is descriptive analysis method and quantitative analysis using multiple linear regression analysis techniques. The results showed that the partial variable organizational commitment was not significant for employee job satisfaction. Organizational culture variables are significant effect to job satisfaction. Work environment variables significant influence to job satisfaction. The variable leadership style is not significant effect to job satisfaction. Simultaneous test results of organizational commitment, organizational culture, work environment and leadership style variables are significantly effect to job satisfaction of PT. BintanBersatu Apparel Batam.